The 5th PSU- USM- International Conference on Arts and Sciences - LKG, Local Knowledge Group (Universiti Sains Malaysia, 2017)
Prince of Songkla University (PSU), Pattani Campus recognizes the importance of its mission to support research grants and activities and deems its responsibility to promote research results undertaken by its staff members, academics, researchers and graduate students. In order to extend its research network for the benefits of academic circles, Prince of Songkla University has sought cooperation from Universiti Sains Malaysia, in organizing the 2017 academic conference. The research theme covers the areas of multi-culturalism, gender and identity, tourisms, economics, education and innovation, natural science and technology, and health science. Participants include keynote speakers, researchers, academics, graduate students and interested public.